Precise Detection, Control and Synthesis of Chiral Compounds at Single-Molecule Resolution - Yang, Chen; Hu, Weilin; Guo, Xuefeng (Nano-Micro Letters, 2023)
Chirality, as the symmetric breaking of molecules, plays an essential role in physical, chemical and especially biological processes, which highlights the accurate distinction among heterochiralities as well as the precise preparation for homochirality. To this end, the well-designed structure-specific recognizer and catalysis reactor are necessitated, respectively. However, each kind of target molecules requires a custom-made chiral partner and the dynamic disorder of spatial-orientation distribution of molecules at the ensemble level leads to an inefficient protocol. In this perspective article, we developed a universal strategy capable of realizing the chirality detection and control by the external symmetry breaking based on the alignment of the molecular frame to external stimuli. Specifically, in combination with the discussion about the relationship among the chirality (molecule), spin (electron) and polarization (photon), i.e., the three natural symmetry breaking, single-molecule junctions were proposed to achieve a single-molecule/event-resolved detection and synthesis. The fixation of the molecular orientation and the CMOS-compatibility provide an efficient interface to achieve the external input of symmetry breaking. This perspective is believed to offer more efficient applications in accurate chirality detection and precise asymmetric synthesis via the close collaboration of chemists, physicists, materials scientists, and engineers. Highlights: 1 Single-molecule electrical detection, especially the single-molecule junction setup, enables the precise detection and spatial operability of anchored molecules. 2 The transition among asymmetric characteristics (i.e., molecular chirality, photonic polarization and electronic spin) is proposed as a universal methodology to realize the detection, control and synthesis of chirality. 3 Exploring the origin of symmetry breaking contributes to the development of a general reliable strategy for asymmetric synthesis.